Les idiomes français utilisant les éléments animaux dans les expressions idiomatiques d’Isabelle Chollet et Jean-Michel Robert - Vera Fitriani; Dies Oktavia Dwi Astuti (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2024)
Semantics is one of the scientific fields of linguistics that studies meaning. There are several types of meaning, one of which is idiomatic meaning. The idiom is a combination of words whose meaning cannot be deduced from the elements that compose them, but rather from the entire expression. This research aims to describe the form and meaning of French idioms used in animal elements in Les Expressions Idiomatiques by Isabelle Chollet and Jean-Michel Robert. This research is qualitative descriptive research. Data were collected using the technique of careful reading and registration. The methods used to analyze the form and meaning of idioms are the equivalent method and the distribution method. The results of this research show that there are one hundred and fifty-five French idioms that use animal elements at the phrase level that have three forms, the three forms are the verbal group, the nominal group, and the adjectival group. All data were analyzed using literal and figurative meaning. Literal meaning is the basic meaning of a word and figurative meaning is the meaning of a word those changes. It is because the word has previously concrete characteristics turned into abstract.